Effect of Recrystallization on the Pharmaceutical Properties of Valsartan for Improved Therapeutic Efficacy - Buchi N. Nalluri, Ramya Krishna M, Rao TP, Peter A. Crooks (Journal of Applied Pharmaceutical Science)
Valsartan (VAL) is a potent, highly selective and orally active antihypertensive drug and is poorly soluble in aqueous fluids, especially in gastric fluids, and its absorption is thus dissolution rate limited. In the present research work an attempt has been made to improve the aqueous solubility of VAL by the recrystallization of VAL from a variety of different organic solvents, and evaluating the recrystallized VAL products for its physicochemical characteristics and in-vitro dissolution properties. The water solubility of methanol (MET), ethanol (ETH), isopropanol (ISP) and acetonitrile (AN) recrystallized products of VAL is significantly higher when compared to untreated VAL. Physicochemical characterization techniques like scanning electron microscopy, differential scanning calorimetry, powder X-RD reveal the change in crystallinity of VAL with recrystallized products and hence the increase in the solubility and superior dissolution properties when compared to the untreated VAL.
Keywords: Valsartan,recrystallization,physicochemcial characterization,dissolution studies